Identificação dos condicionantes para a criação de consórcios intermunicipais: estudo de caso na região nordeste do estado de São Paulo - Strazza, Mariane de Carvalho (2018)
In order to fulfill the commitments established due to the promulgation of The National Solid Waste Policy (NSWP – Política Nacional de Resíduos Sólidos - PNRS), The Federal Government, Federal District, States and Municipalities should elaborate and implement their Integrated Management Plans of Solid Waste, aiming to guarantee the adequate environmental handling of these wastes. It occurs that, most Brazilian municipalities, with emphasis on the small ones, do not have qualified technical staff or financial resources to implement management solutions to cater to all the parameters imposed by national policy. Despite this aspect, The NSWP motivates the adoption of consortiums as a management instrument of the handling chains of the wastes, which is why this research has sought to identify if the creation of an intercity public consortium aimed at the proper environmental management of solid waste, would assure the municipalities enough tools to confront all these challenges proposed by The NSWP. In order to do so, it has been performed a study of the municipal plans of integrated management of solid wastes, and/or the basic sanitation municipal plans of nine municipalities from the northeast region of Sao Paulo state, interviews not structured with the environmental Municipal Departments, desk researches about public consortiums and a case study of public consortiums of waste management in operation, the result has shown that, intercity cooperation really furnish locals with instruments to deal with the proper environmental handling of solid wastes and, therefore, it has been proposed the elaboration of a public consortium among locals who are participating in this research through the presentation of the preliminary version of the protocols of intentions.